Patterns of cladogenesis in the venomous marine gastropod genus Conus from the Cape Verde islands - Cunha, R. L. (2014)
Isolated oceanic archipelagos are excellent model systems to study speciation, biogeography, and evolutionary factors underlying the generation of biological diversity. Despite the wealth of studies documenting insular speciation, few of them focused on marine organisms. Here, we reconstruct phylogenetic relationships among species of the marine venomous gastropod genus Conus from the Cape Verde archipelago. This small island chain located in the Central Atlantic hosts 10% of the worldwide species diversity of Conus. Analyses were based on mtDNA sequences, and a novel nuclear marker, a megalin-like protein, member of the low-density lipoprotein receptor gene family. The inferred phylogeny recovered two well-defined clades within Conus. One includes Cape Verde endemic species with larger shells, known as the “venulatus” complex together with C. pulcher from the Canary Islands. The other is composed of Cape Verde endemic and West Africa and Canary Island “small” shelled species. In both clades, nonendemic Conus were resolved as sister groups of the Cape Verde endemics, respectively. Our results indicate that the ancestors of “small” and “large” shelled lineages independently colonized Cape Verde. The resulting biogeographical pattern shows the grouping of most Cape Verde endemics in monophyletic island assemblages. Statistical tests supported a recent radiation event within the “small shell” clade. Using a molecular clock, we estimated that the colonization of the islands by the “small” shelled species occurred relatively close to the origin of the islands whereas the arrival of “large” shelled Conus is more recent. Our results suggest that the main factor responsible for species diversity in the archipelago may be allopatric speciation promoted by the reduced dispersal capacity of nonplanktonic lecithotrophic larvae.